A Cinderella seduction - Booth, Karen (Karen B.) (Booth, Karen (Karen B.) Eden Empire., 2019)
"Discovering she's a member of Manhattan's most famous retail dynasty has given Emma Stewart a place to belong. Meeting a seductive stranger makes her rags-to-riches transformation complete. But British-born heir Daniel Stone is secretly carrying out revenge against her new family. Now the clock is ticking down to midnight on their secret affair ..."--Back cover.